Effects of reducing postprandial hyperglycemia and metabolism of acetate wheat starch on healthy mice (Brazilian Journal of Pharmaceutical Sciences, 2023)
Recently, the acetate wheat starch (AWS) has been prepared by acetylation with an acetyl content of 2.42%, containing of rapidly digestible starch (RDS), slowly digestible starch (SDS) and resistant starch (RS) with 25.0%; 22.9% and 34.5%, respectively. In this study, this kind of starch was continuously evaluated with the postprandial blood glucose response and determined short-chain fatty acids (SCFAs) metabolized from AWS in the gastrointestinal tract of healthy mice by HPLC. The result showed that the mice fed with AWS exhibited a very limited increase in blood glucose level and remained stable for 2 hours after meals efficiently comparing with the control group fed with natural wheat starch (NWS). Simultaneously, the content of SCFAs produced in the caecum of the mice fed with AWS was significantly higher than mice fed with NWS, especially with acetic and propionic acids by 28% and 26%, respectively. Thus, AWS has shown to limit the postprandial hyperglycemia in mice effectively through the resistance to amylase hydrolysis in the small intestine. When going into the caecum, it is fermented to form SCFAs providing a part of energy for the body’s activities, avoiding rotten fermentation causing digestive disorders which are inherent restrictions of normal high cellulose and fiber food.